Artificial Intelligence from Economic Perspective: From Mystery to Mastery in Combating The COVID-19 Pandemic - Andreea-Cristina BOERU; Anca Gabriela ILIE (Communications of International Proceedings, 2022)
Digital technology is all around us, but how did we perceive its benefits during the COVID-19 outbreak? It is known that countries worldwide, due to COVID-19 spread reacted immediately and took unitary agreed decisions. Assuming that artificial intelligence constitutes a weapon in the battle against the pandemic, this article aims to explain its implication during the first 17 months of the outbreak (December 2019- May 2021) by defining the methods that have been used. This article should provide an overview of the public view regarding the pandemic situation of the EU27 and non-EU countries after analyzing European Commission reports. Furthermore, a comparison of the European Union and non-European Union member states with the United States of America has been made to emphasize the general attitude of the citizens regarding the use of digital technologies.
Keywords: artificial intelligence; COVID-19; pandemic; EU27